The role of green and digital marketing in driving impulsive buying - Prasetyo, Johan Hendri; Wiharso, Gani (Jurnal Mantik, 2025)
Consumer awareness of environmental issues has driven businesses to adopt green and digital marketing strategies to influence purchasing behavior. This study examined the impact of green marketing and digital marketing on impulsive buying, focusing on environmentally friendly product attributes, sustainability-focused promotions, social media engagement, and influencer endorsements. Using a quantitative approach, data were collected from 210 respondents through purposive sampling and analyzed using multiple regression analysis. The results showed that green marketing had a significant positive effect on impulsive buying (? = 0.742, p = 0.000), while digital marketing also significantly influenced impulsive buying (? = 0.342, p = 0.005). Moreover, the combined effect of green and digital marketing was statistically significant (F = 92.71, p = 0.000), with an R² value of 0.645, indicating that 64.5% of the variance in impulsive buying was explained by both variables. These findings suggest that integrating sustainability initiatives with digital engagement enhances impulsive purchasing tendencies. However, this study is limited by its sample characteristics and the exclusion of moderating factors such as financial constraints and brand loyalty. Future research should explore these aspects and assess the long-term impact of green and digital marketing on impulsive buying